Development of a VP38 recombinant protein‐based indirect ELISA for detection of antibodies against grass carp reovirus genotype II (iELISA for detection of antibodies against GCRV II). Issue 12 (26th September 2018) - Zeng, Weiwei; Wang, Yingying; Guo, Yanmin; Bergmann, Sven M.; Yin, Jiyuan; Li, Yingying; Ren, Yan; Shi, Cunbin; Wang, Qing
Abstract: Currently, serological assays for grass carp reovirus genotype II (GCRV‐II) diagnosis are not available. In this study, an indirect enzyme‐linked immunosorbent assay (ELISA) for the detection of antibodies against GCRV‐II was developed. The structural protein VP38 of GCRV‐II was used as the coating antigen. Monoclonal antibodies (mAb) against IgM of grass carp labelled with HRP were used as a secondary antibody. The antigen concentration and serum dilution were optimized using chess board titration. Furthermore, the specificity of indirect ELISA assay was confirmed by cross check with sera positive for other grass carp pathogens. In comparison with results obtained from indirect immunofluorescence assay (IFA) and Western blot by testing of 60 serum samples to evaluate the sensitivity and specificity of the ELISA, agreement between 90% and 96.7% was reached, respectively. A serological survey was performed using the assay with grass carp field serum samples. The seropositive rate of the 242 serum samples was 69.8%. In conclusion, the developed indirect ELISA is a very specific and sensitive test that will be useful for large‐scale serological surveys to detect indirectly GCRV II infections as well as to monitor the changes of antibody level after immunization.